(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In this article, as a result of studying the foreign experience of taxing the profits of legal entities, the issues of improving the legal base in our country were studied and studied in depth the organizational forms, legal organization and importance in the development of the economy. Also, the trend of development of taxation of the profits of legal entities in mamlkatim, the state of which it is today, has been analyzed on the basis of accurate data.